Quality and cost of healthcare services in patients with diabetes in Iran: Results of a nationwide short-term longitudinal survey - Abbasi-Kangevari, Mohsen; Mohebi, Farnam; Ghamari, Seyyed-Hadi; Modirian, Mitra; Shahbal, Nazila; Ahmadi, Naser; Farzi, Yosef; Azmin, Mehrdad; Roshani, Shahin; Zokaei, Hossein; Khezrian, Maryam; Seyfi, Shahedeh; et al. (Frontiers in Endocrinology, 2023)
Aims: To investigate the journey of patients with diabetes in the healthcare system using nationally-representative patient-reported data. Methods: Using a machine-learning-based sampling method based on healthcare structures and medical outcome data, participants were recruited and were followed up for three months. We assessed the resource utilization, direct/indirect costs, and quality of healthcare services. Results: 158 patients with diabetes participated. The most utilized services were medication purchases (276 times monthly) and outpatient visits (231 times monthly). During the previous year, 90% of respondents had a laboratory fasting blood glucose assessment in the previous year; however, less than 70% reported a quarterly follow-up physician visit. Only 43% had been asked about any hypoglycemia episodes by their physician. Less than 45% of respondents had been trained for hypoglycemia self-management. The annual average health-related direct cost of a patient with diabetes was 769 USD. The average out-of-pocket share of direct costs was 601 USD (78.15%). Medication purchases, inpatient services, and out-patient services summed up 79.77% of direct costs with a mean of 613 USD. Conclusion: Healthcare services focused solely on glycemic control, and the continuity of services for diabetes control was insufficient. Medication purchases, and inpatient and outpatient services imposed the most out-of-pocket costs.